2020
DOI: 10.1177/1066480720929360
|View full text |Cite
|
Sign up to set email alerts
|

The Widowhood Effect: Explaining the Adverse Outcomes After Spousal Loss Using Physiological Stress Theories, Marital Quality, and Attachment

Abstract: The loss of a loved one is one of the most ubiquitous life experiences. There have been multiple reviews that have found adverse health outcomes for individuals experiencing spousal loss, particularly the widowhood effect that characterizes an increased risk of mortality after loss. However, there is a lack of clarity on the relationship between physiological stress and the widowhood effect. This commentary uses the literature on stress, marital quality, and attachment to explain the widowhood effect and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…This form of cognitive reframing and assimilation can also result in fewer episodes of intrusive thoughts and images. Intrusive thoughts can contribute to the distress experienced by the suicidebereaved and are also a common symptom of complicated grief, thus, addressing this issue is vital in minimizing bereavement stress (Ennis & Majid, 2020). Dunn and Morrish-Vidners (1987) found that respondents in their study seemed eager to talk in detail.…”
Section: Unexpected Trauma and The Assumptive Worldmentioning
confidence: 97%
“…This form of cognitive reframing and assimilation can also result in fewer episodes of intrusive thoughts and images. Intrusive thoughts can contribute to the distress experienced by the suicidebereaved and are also a common symptom of complicated grief, thus, addressing this issue is vital in minimizing bereavement stress (Ennis & Majid, 2020). Dunn and Morrish-Vidners (1987) found that respondents in their study seemed eager to talk in detail.…”
Section: Unexpected Trauma and The Assumptive Worldmentioning
confidence: 97%
“…For example, one study found that caregivers of terminally ill patients had higher mortality when their family did not use hospice services compared to those who did, indicating that caregiving confers unwanted burden that might also impact the physical health of caregivers (Christakis & Iwashyna 2003). While chronic physiological stress may cause an increased risk of adverse physical health outcomes, the quantity and quality of resources available to the grieving caregiver as well as the relationship between caregiver and their loved one may explain why certain adverse physical health outcomes persist years after loss (Ennis & Majid, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Losing a spouse to death is a life-changing event, with varying implications for survivors. In addition to grief over losing a loved one, bereaved spouses' sense of loss may be compounded by multiple stressors stemming from spousal death, such as loneliness, taking on new roles and responsibilities (e.g., being a single parent and a breadwinner), and adjusting to the reality of losing a primary support system in the deceased spouse (e.g., Lowe and McClement, 2010;Ennis and Majid, 2020). Social support is one of the key resources for surviving spouses when coming to terms with spousal death.…”
Section: Introductionmentioning
confidence: 99%